Participação popular na política municipal de habitação no Município de Vitória/ES - Delanos, Flaviane Cristina de Oliveira Ferreira (2011)
The main concern of this study was to understand how the population has participated in the formulation and implementation of housing policy in Vitória/ ES. We followed a scientific career in pursuit of knowing how the population has occupied the space for discussion / formulation of housing policy, to characterize how the population has been interfering in municipal housing policy, and identify the limits and challenges of social participation in the formulation of housing policy and whose interests were served in the formulation and implementation of housing policies. This research was supported by a methodology that sought to collect and organize data in a qualitative empirical data and articulating theoreticalexplanatory. This means that reflection and the empirical observation of the data was dialectically united for a better understanding of the phenomenon being studied. So, the method of study is critical, dialectical, supported by historical materialism. It is a case study, which used a literature review, research documents and individual interviews with board members representing the population in CMHIS with the executive secretary of the board, a City Attorney and the current manager SEHAB from a semi-structured data collection. Data interpretation was possible, through content analysis. As a theoretical discussion worked with a design of urban space constructed from the logic of capitalist society. With this context envolves a housing policy necessary to achieve a social right, founded on democracy and popular participation, guaranteed by the process of democratization in Brazil, whose main protagonists were the urban social movements. However, this policy is crossed by a neoliberal logic, causing discontinuities and limits concerning its establishment and operation of instances of participation, especially in management councils. The reality of urbanization in the city of Vitória/ ES inflections also suffered over time, impacting on the local democratic participation, as well as the construction of housing policy. As a result we identified the presence of people in the construction of the policy. We have seen what determines the share is exactly the kind of democracy. We identified the prevalence of a relationship that plays the representative model. We can say from this study that there was participation in the construction of housing policy in the city of Vitoria. However, this participation was more intense from the time the policy was put into operation, in other words, when the PMV began its work plan, to take the steps that led to the implementation of substantive policy.